ANALYSIS OF THE IMPLEMENTATION GRC INFORMATION SYSTEM IN SUPPORTING PERFORMANCE OPTIMIZATION - Ketin Febrina Adisuria; Riyanto Jayadi (Journal of Information System Management (JOISM), 2023)
The Integrated Governance and Compliance Risk Information System (SIGRC) is critical in helping institutions achieve their goals and deal with uncertainty. An Indonesian Government Agency (IGA) has used SIGRC for years. However, its utilization is still unknown. This research studies the impact of acceptance and utilization of SIGRC using Delone McLean and Unified Technology Acceptance and Use Technology. The conclusion is that the relationship between use and net benefits is unaffected. User intention on use, performance expectations on user intention, use on user satisfaction, and user satisfaction on the net benefit of SIGRC benefits are five factors that influence user satisfaction. While the expectation of use intention (ITU). Information quality with ITU. Quality of service with the use of ITU. Service quality with user satisfaction, system quality with ITU, and system quality with user satisfaction all have an influence but are not significant. This research is expected as a guideline for others to evaluate the effectiveness of SIGRC's performance. Keywords: GRC Software, Delone & Mclean, UTAUT, Decision Support System, Evaluation Information System